Social Violence and it's influence on displaced families children offensive behavior (field study of displaced families children out side the immigrate centers in Lattakia city) - Omran, Hani; Ahmed , Hamsah (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
From these study it was shown that there are direct relationship between the offensive behavior of displaced families students , and the family violence, where it was shown that the offensive behavior of students is the defection act of another action of family violence in side the displaced families , and we fined different types of family violence toward against children , and it was shown that there are different between boys and girls from there reactions , where there are statistic index differ on the offensive behavior scale for boys in the step 0.0005 . which correspond with the social teaching theory, where the offensive behavior of sons is the emulation natural results, and imitation response offensive behavior of parents against them like a chastisement, and self supersensible pain, and sufferance, and others sorts of violence.